(untitled) (Bangladesh Journal of Anatomy, 2019)
Context: Facial Anthropometry is affected by geographical, racial, ethnical, gender and age factor. Facial phenotype is modified in several genomic and chromosomal alteration. Anthropometric study plays an important role in distinguishing pure race from local mingling of races. Anthropometric data is important for plastic surgery, orthodontics, archeology, hair style design and application in medical and clinical genetics. The present study aimed at establishing ethnic specific anthropometric data for the Bangladeshi Khasi population and to compare it with non-tribal population. Methods: The present study was conducted on facial variables of 100 Khasi and 100 non-tribal Bangladeshi male. Photographs of face were taken by digital camera and different dimentions were measured with computer programmed MB-Ruler software. Comparisons of the measurements between Khasi and nontribal were done by using an unpaired student’s ‘t’ test. Result: The mean±SD of morphological facial height, upper facial width and mean facial index of Khasi male were10.98±0.65 cm, 11.72±0.49cm and 90.61±6.12cm respectively. The mean±SD of morphological facial height, upper facial width and mean facial index of non-tribal male were 11.63±0.53 cm, 11.52±0.56cm and 95.45±3.95 cm respectively. Conclusion: Significant difference was observed in facial index between Khasi and non-tribal population. Bangladesh Journal of Anatomy July 2019, Vol. 17, No. 2, pp. 36-39